2018
DOI: 10.1088/1361-6439/aacf5c
|View full text |Cite
|
Sign up to set email alerts
|

Suspended GaN beams and membranes on Si as a platform for waveguide-based THz applications

Abstract: Epitaxial growth of ultra-thin NbN films on AlxGa1-xN buffer-layers S Krause, D Meledin, V Desmaris et al. IntroductionThe exploration of the THz frequency range is constantly gaining speed and numerous applications have emerged within research, security, astronomy, biomedicine and metrology in recent years [1][2][3]. The main reason for this relatively late development can be attributed to several technological challenges that had to be overcome. As the dimensions of microwave components usually scale with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…with gds=1/Rds. Tg and Td are the only unknowns in (5), and are treated as fitting parameters. Since the four noise paraments of the device are derived from its noise correlation matrix, they can also be expressed as function of Td and Tg.…”
Section: Table I Instrumentation Uncertainties In the Measurement Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…with gds=1/Rds. Tg and Td are the only unknowns in (5), and are treated as fitting parameters. Since the four noise paraments of the device are derived from its noise correlation matrix, they can also be expressed as function of Td and Tg.…”
Section: Table I Instrumentation Uncertainties In the Measurement Of ...mentioning
confidence: 99%
“…In particular, the choice of the transistors can be a key determinant of the overall noise performance of the radio-astronomy receivers [4]. In addition to their potential natural integration with heterodyne mixers [5] [6], the superior linearity and dynamic range of GaN HEMTs over conventional technologies make them very attractive for radio-astronomy cryogenic instrumentation and inherently excellent robustness against Radio Frequency Interference (RFI). M.A.…”
Section: Introductionmentioning
confidence: 99%
“…3) Previous GaN MEMS devices reported to date were fabricated by the heteroepitaxial growth of a GaN film on a silicon (Si) substrate, which contains a higher dislocation density than that grown on a free-standing GaN substrate. [4][5][6][7][8][9][10] It was reported that the lower dislocation density increases the quality factor of MEMS devices. 11) Furthermore, GaN MEMS devices on free-standing GaN substrates are more advantageous MEMS devices for use in harsh environments than those grown on Si substrates.…”
mentioning
confidence: 99%